An evidence based approach to technology roadmapping - Sheila Price (2012)
The aim of this study was to investigate the role of technology roadmapping within commercial and industrial domains at a sector or industry wide level, and to develop an information model that could be used to enhance the generic technology roadmapping process. The study focused on the development of version three of the Foresight Vehicle technology roadmap to support the development of low carbon vehicles in a global marketplace. The development of a ‘real’ sector level technology roadmap enabled ideas in relation to data collection elements to be tested, especially in terms of personnel, participants and publication channels. The various tools currently used to develop technology roadmaps were identified and assessed for their suitability for use in this study. A mixture of data collection techniques were used to generate data and investigate the process of developing a core data set, associated data, as well as the identification of the relationship between potentially disparate items of information. FV Thematic Group members took part in workshops to elicit data, inform the evolution of the data collection process and inform the development of the information protocol. Results from the data collection exercise indicated that not all technology issues were technology focused, non technology issues presented a challenge not only in terms of representation but of ownership as well. Tools such as Technology Readiness Levels were adapted and utilised to create a ‘rich picture’ of multi-dimensional and customised roadmap views. The study presents an information protocol to support the development of technology roadmaps primarily in a digital format and considers elements such as data collection, information management, preservation, representation, scope and validation,. The findings of this study suggest that the development of a generic information model to support the technology roadmapping process is timely and that inclusion of all elements of the protocol lead to the development of a technology roadmap that is fit for purpose.